2010
DOI: 10.1007/s12033-010-9277-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel Expression System for Combined Vaccine Production in Edwardsiella tarda Ghost and Cadaver Cells

Abstract: To develop combined vaccine systems, we have generated Edwardsiella tarda ghosts (ETG) displaying a foreign protein on the outer membrane and also Ed. tarda cadaver (ETC) expressing a heterologous protein in the cytoplasm. Green fluorescent protein (GFP) was used as a model foreign protein. A constitutive promoter (EtPR C28-1) cloned newly from Ed. tarda was used as a promoter for the expression of foreign protein. Comparison of the strength of the new promoter with a commercially available constitutive promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…The asd gene expression was driven by a weak constitutive promoter (G02) that was selected from the previously constructed E. tarda promoter trap library [40]. Briefly, the putative promoter region (G02) was PCR-amplified by using a pair of primers (G02 AatII F and G02 SpeI R), cloned into pGEM-T vector, and sequenced for confirmation.…”
Section: Construction Of Antibiotic Resistance Gene-free and Heterolomentioning
confidence: 99%
See 2 more Smart Citations
“…The asd gene expression was driven by a weak constitutive promoter (G02) that was selected from the previously constructed E. tarda promoter trap library [40]. Briefly, the putative promoter region (G02) was PCR-amplified by using a pair of primers (G02 AatII F and G02 SpeI R), cloned into pGEM-T vector, and sequenced for confirmation.…”
Section: Construction Of Antibiotic Resistance Gene-free and Heterolomentioning
confidence: 99%
“…The antibiotic resistance gene (Amp R ) in pG02-ASD was removed by digestion of the plasmid with DraI and NarI, then a sequence containing multiple cloning sites (DraI-BglII-NcoI-ScaI-NsiI-NarI) was inserted into the digested plasmid, resulting in pG02-ASD-MCS. The GFP expressing cassette driven by a strong constitutive promoter (EtPR C28-1) of E. tarda [40] was cut by digestion of plasmid pEtPR-GFP with ApaI and NsiI, then, ligated to the pG02-ASD-MCS, and designated as pG02-ASD-EtPR-GFP.…”
Section: Construction Of Antibiotic Resistance Gene-free and Heterolomentioning
confidence: 99%
See 1 more Smart Citation
“…Now, researchers are looking into developing vaccines to tackle its epizootics. Recently, a few effective vaccines have been developed viz., E. tarda ghosts (Kwon et al 2006;Choi et al 2010), rifampicin-resistant strains (Evans et al 2006;Sun et al 2010), recombinant GAPDH (Liu et al 2007), and mutants for esrB gene (Lan et al 2007), with variable success but these are yet to be commercialized. In such conditions, selective breeding seems to provide the most promising solution to the disease problem.…”
Section: Introductionmentioning
confidence: 99%
“…For surface display of antigens in bacterial ghosts, the ice nucleation protein (6) and various outer membrane proteins, such as outer membrane protein A, have been used as anchors (12,13). Recently, it has been shown that antibody responses to heterologous antigens that are secreted by Salmonella cells or exposed at the surface of Salmonella-derived outer membrane vesicles (OMVs) are higher than antibody responses to antigens that are present intracellularly or in the lumen of the OMVs, respectively (e.g., see references 14 to 16).…”
mentioning
confidence: 99%